Subjective experience, cognitive functioning and trauma level of patients undergoing awake craniotomy due to brain tumor - Preliminary study. Issue 5 (3rd September 2022) - Starowicz-Filip, Anna; Prochwicz, Katarzyna; Myszka, Aneta; Krzyżewski, Roger; Stachura, Krzysztof; Chrobak, Adrian Andrzej; Rajtar-Zembaty, Anna Maria; Bętkowska-Korpała, Barbara; Kwinta, Borys
Abstract: Backup and objective: Awake craniotomy (AC) for brain tumors, when the patient is conscious during the operation, allows to reduce the risk of motor disability and aphasia, however, it may be a source of extreme stress. The aim of our study was to examine the patients' subjective experience of the surgery including the level of psychological trauma and cognitive functioning. Method: Eighteen patients operated due to brain tumor were enrolled in this study. The Essener Trauma-Inventory Questionnaire and the Addenbrooke's Cognitive Examination (ACE III) were administrated. The patients' experience with awake craniotomy was evaluated with a qualitative descriptive survey. Results: All patients remembered the intraoperative neuropsychological examination and several sensations like: drilling, cold, head clamp fixation or having eyes covered. In most of the patients the postoperative psychological trauma experience did not reach the clinical level. The ACE III postoperative scores revealed partial cognitive deficits with the lowest scores in memory and word fluency domains. Slight amnestic aphasia was observed postoperatively only in two patients. Conclusions: Awake craniotomy for resection of brain tumors is well-tolerated by patients and does not cause significant psychological trauma. Nonetheless, anxiety about the procedure warrants further study and individualized neuropsychological care is needed for the emotional preparation of the patient.